Quantum Imaging of Biosamples - Grenapin, Florence (Université d'Ottawa / University of Ottawa, 2023)
All far-field optical imaging is limited by diffraction from optical elements, a phenomenon called Rayleigh's curse. It has been shown that through the use of the spatial mode demultiplexing technique (SPADE), an arbitrarily small separation between two point sources can be resolved, given a sufficiently large total number of photons N. This quantum metrology approach to super-resolution has since then been demonstrated and generalized to more complex situations. We propose a variant of SPADE, that we call biphoton SPADE, applied to imaging systems with spatially entangled photon pairs generated through spontaneous parametric downconversion. Our method can achieve a higher precision than SPADE, given any non-zero level of entanglement. We furthermore demonstrate our technique in a coincidence imaging setup and show super-resolution while only projecting on a select few of the total optimal modes in the 2D joint basis. Since the method uses quantum light and provides even further sensitivity to SPADE, it can potentially be used in the future for various light-sensitive imaging applications and in combination with neural networks. In nature, one often finds structures that have only been replicated by humans through years of precise, state-of-the-art engineering. Polymer spherulites, naturally occurring birefringent crystals that grow around defects in a radial pattern, are an example of this. We show through the example of ascorbic acid, commonly referred to as Vitamin C, that spherulites are capable of creating beams with orbital angular momentum (OAM) through a process called spin-to-orbit coupling. This action of the ascorbic acid crystals is analogous to the one of spatially structured waveplates called q-plates, which are built to have an azimuthally dependant optic axis. This opens the door for potentially cheaper fabrication of q-plates, and possibilities of tuning the growth of the molecules for arbitrary wavefront shaping with natural crystals. Finally, because of the wide range of crystals in the spherulite class, further investigation into different spherulites could shed light on the relationship between crystal symmetry and structure, and the shaping of light.
Keywords: Super-resolution; Spherulite; PBOE; Entanglement